E-generation: a new model for educational intranets - Alves, Paulo (2010)
The adoption of ICTs in the higher education is a slow and complicated process, which depends of many factors. Despite de technical and technological issues, the motivation of teachers and students are the most relevant factors of success. The Escola Superior de Tecnologia e de Gestão (ESTIG) of Instituto Politécnico de Bragança, develops in 1999 an e-learning platform named Domus, with similar characteristics like WebCT or Learning Space. After two years of usage, the number of teachers that adopt the platform in their classes was very low. With the objective to stimulate the use of ICTs in learning, teaching and management, it was designed a new model for an educational Intranet, integrating technologies like e-learning, e-management, groupware, workflow and agents. The main objective of this Intranet is to dispose a unique Web environment for all pedagogical and administrative tasks. This paper presents the framework developed to support the Intranet, integrating several services and using new technologies for the interoperability between information systems. The integration of the sector-based data marts in the Intranet was made passing to a data warehouse philosophy, using agents to replicate data. The integration of e-learning in this process was made developing the most important services for teachers and administrative staff, having in mind the postulate that the necessity lead to the usage.